القيادة السامة وأثرها على الالتزام التنظيمي "دراسة حالة على عينة من العاملين بمركز بنغازي الطبي" - د. رجعة المبروك الفاخري (Sharwes Scientific Journal, 2025)
The study aimed to determine the level of toxic leadership, as well as to identify the level of organizational commitment. It also aimed to identify the impact of toxic leadership on organizational commitment at Benghazi Medical Center. The researchers adopted a case study approach and used a questionnaire as a tool for collecting the necessary data. The study population consisted of (220) employees, and the sample size was determined using the Krejcie and Morgan table (1970), reaching (134) individuals. A simple random sampling technique was used to select the sample. After distributing the questionnaire, (125) valid questionnaires were retrieved for statistical analysis. To analyze the study data, a computer was used, and a statistical program from the SPSS software suite was employed. The study revealed several key findings, including a significant impact of toxic leadership on organizational commitment. Through multiple regression analysis, the results showed that the dimensions of "abusive supervision" and "autocratic leadership" significantly contributed to the level of organizational commitment, while the remaining dimensions, namely "narcissism," "self-promotion," and "difficulty in predicting," did not contribute to the level of organizational commitment. In light of these findings, the study presented several recommendations, the most important of which is to strive for a clear understanding of toxic leadership behaviors among all employees through conducting seminars and training courses to deepen the understanding of such behaviors while explaining the forms and patterns of positive leadership. Additionally, efforts should be made to reduce toxic leadership behaviors in the study units to minimize the waste of time, financial resources, and human capital.